Implementation of strengthening short letter memorization through outbound fun games at MI Maarif Asmaul Husna Kemloko, Kranggan, Temanggung - Farinka Nurrahmah; Eka Mahargiani Rokhma; Istiqomah; Fouad Larhzizar; Zainal Arifin (At Turots: Jurnal Pendidikan Islam, 2024)
This research aims to describe the implementation of outbound fun games in strengthening short letter memorization for students at MI Maarif Asmaul Husna Kemloko Kranggan. This research uses a qualitative descriptive method by presenting data in the form of facts documented from interviews, observations and data interpretation. Initial observations stated that students' initial abilities still need to be strengthened because they are still not optimal and teachers still use memorization methods that are not yet varied and fun. The results of this research are that outbound fun games can strengthen the memorization of short letters because students are more motivated to be able to answer quizzes in the outbound game so that they emerge as the winning group, while other findings state that some students who failed to memorize the short letters they received enthusiastically repeated their memorization in order to be able to pass the challenges so that the journey in the outbound Fun Game can be completed well. Apart from that, there are many positive contributions regarding the use of outbound in learning, not only in deepening concepts but also towards independence. Cooperation, leadership, and the students' compassions for the surrounding environment.